2007
DOI: 10.1007/s10236-006-0099-5
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the classical and extended Rossby wave theories in explaining spectral estimates of the first few baroclinic modes in the South Pacific Ocean

Abstract: Previous literature has suggested that multiple peaks in sea level anomalies (SLA) detected by twodimensional Fourier Transform (2D-FT) analysis are spectral components of multiple propagating signals, which may correspond to different baroclinic Rossby wave modes. We test this hypothesis in the South Pacific Ocean by applying a 2D-FT analysis to the long Rossby wave signal determined from filtered TOPEX/Poseidon and European Remote Sensing-1/2 satellite altimeter derived SLA. The first four baroclinic mode di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 33 publications
5
56
2
7
Order By: Relevance
“…While the extended theories appear to do better than the SLT at reducing the discrepancy with observations, e.g., Maharaj et al (2007), this does not necessarily mean that they do so for the correct reasons. This is because the extended theories, despite their apparent success, still rely on a number of assumptions whose validity can neither be directly checked against observations, nor rigorously proven mathematically.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…While the extended theories appear to do better than the SLT at reducing the discrepancy with observations, e.g., Maharaj et al (2007), this does not necessarily mean that they do so for the correct reasons. This is because the extended theories, despite their apparent success, still rely on a number of assumptions whose validity can neither be directly checked against observations, nor rigorously proven mathematically.…”
mentioning
confidence: 86%
“…Challenor et al (2001) applied a 3-D RT on altimeter data in the North Atlantic and showed that the meridional phase speed was negligible in many places; this justifies why only the 2-D RT is used here. Some authors (Subrahmanyam et al, 2000;Osychny and Cornillon, 2004;Maharaj et al, 2007) have used the 2-D Fourier Transform instead of the 2-D RT. This alternative approach highlights the spectral components of the data in time and space and provides a different estimate of superimposed phase speeds.…”
mentioning
confidence: 99%
“…Second, a three-layer model is the simplest that will capture modal interactions correctly [see Dewar and Morris (2000), who explicitly advocate the use of three-layer models]. Third, Maharaj et al (2007) have shown that, at least in the South Pacific, two baroclinic modes suffice to explain almost all the observed variability of sea surface height. They see hardly any third mode, which would in any case be very poorly resolved on the 10-km grid used in this study.…”
Section: Modelmentioning
confidence: 99%
“…The main objective of this paper is twofold: 1) to clarify the nature of the error and show how to redress it and 2) to understand how the error affects some of KB04's conclusions regarding the nature of the dispersion relation of Rossby waves in the presence of a background mean flow and topography. The issue is important to clarify because it also affects KB05's results and KB07's discussion of forced modes and baroclinic instability and is expected to alter some of the conclusions of the comparison of the KB04 theoretical dispersion relations against observations recently carried out by Maharaj et al (2007Maharaj et al ( , 2009.…”
Section: Introductionmentioning
confidence: 99%